Health benefits and potential applications of anthocyanins in poultry feed industry. Issue 2 (12th March 2018) - CHANGXING, L.; CHENLING, M.; ALAGAWANY, M.; JIANHUA, L.; DONGFANG, D.; GAICHAO, W.; WENYIN, Z.; SYED, S.F.; ARAIN, M.A.; SAEED, M.; HASSAN, F.U.; CHAO, S.
Abstract : Anthocyanins are flavonoids widely spread in various plant species as a major phyto-pigment. In recent years, interest in using anthocyanins as a feed ingredient has increased markedly owing to their health and other benefits. Anthocyanins possess various pharmacological properties, including anti-inflammatory, immunomodulatory, anticancer, antidiabetic, neuroprotective, anti-obesity and antioxidant effects. Dietary consumption of anthocyanins has revealed benefits in animal performance. Little is known about health-promoting effects of anthocyanins in avian species, but anthocyanin-rich dried fruits have shown positive effects on certain pathological conditions and health promoting markers in human and other animals. This review aims to gather information regarding health benefits of anthocyanins and highlight therapeutic and potential health beneficial effects of anthocyanins for poultry. Additionally, it explores these biologically important flavonoids as alternative ingredients in poultry feed to replace synthetic nutrients and medicines. The available literature reports studies involving use of anthocyanins focused on human, mice and in vitro models. However, there is a need to explore mechanism of action at molecular level to understand potential beneficial effects of anthocyanins in avian species.